(untitled) (Quaderni di Gargnano, 2018)
A long polemical letter about the Sack of Rome, composed in 1528 a few months after the printing of The Courtier and directed against Alfonso de Valdés, was to be Baldassarre Castiglione’s last literary work. While the letter epitomizes and embodies the value system developed in Castiglione’s major work, the harsh tone distinguishes it from his other compositions. The paper looks at the political and diplomatic situation at the heart of the controversy between the two correspondents and considers how their practical goals shaped the formal and stylistic tone of their exchange.